Convalescent hyperimmune plasma for chemo-immunotherapy induced immunodeficiency in COVID-19 patients with hematological malignancies - Ferrari, Silvia (Leuk Lymphoma, 2021)
During the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) outbreak, patients with defective immunity after chemo-immunotherapy due to hematological disorders showed prolonged symptoms and worse prognosis of coronavirus disease-2019 (COVID-19) pneumonia, probably due to inadequate adaptive immune response and noneffective viral clearance. We describe a single-center series of hematological immunocompromised patients undergoing passive immunization with hyperimmune plasma for persistent COVID-19 symptoms. In all cases, such treatment was well tolerated and contributed to clinical and radiological improvement and recovery; viral clearance was also achieved in a patients’ subset. Although requiring further investigation, these results suggest a specific role for hyperimmune plasma administration in hematological patients.